Worker participation in the management of occupational safety and health: qualitative evidence from ESENER-2. Country report: Greece (Luxembourg, 2017)
"The study focuses on the representation of workers’ interests in health and safety as experienced by representatives themselves, by their fellow workers and by their employers and managers. It is based on in-depth interviews with these participants in 143 different establishments in seven EU member states: Belgium, Estonia, Greece, the Netherlands, Spain, Sweden and the United Kingdom. The large majority of the cases are establishments that were surveyed in ESENER-2. They were drawn equally from three main sectors – private production, the public sector and private services- and three size classes - small, medium and large-. Their analysis was supported by a review of the literature and additional interviews with informants in key organisations, as well as by a further quantitative analysis of relevant ESENER-2 data."